Heart rate variability threshold values for early-warning nonfunctional overreaching in elite female wrestlers - Tian, Y.; He, Z. H.; Zhao, J. -X.; Tao, D. -L.; Xu, K. -Y.; Earnest, C. P.; Mc Naughton, L. R. (The Journal of Strength and Conditioning Research, 2013)
Functional overreaching (FOR) represents intense training followed by a brief reduction in performance and then a rapid recovery (<2 weeks) and performance supercompensation. Nonfunctional overreaching (NFOR) occurs when the reduced performance continues ?3 weeks. Heart rate variability (HRV) is a promising tool for detecting NFOR. In this study, the authors examined HRV thresholds in 34 elite female wrestlers (mean ± SD: age 23 ± 3 years; height 165.6 ± 6 cm, weight 63 ± 8 kg) for FOR/NFOR during training before 11 major competitions. Supine HRV was analyzed weekly at the same time of day using time and frequency domain methods. The authors observed that the time domain index, square root of the mean of the sum of the squares of differences between adjacent R-to-R intervals (rMSSD, milliseconds), denoting parasympathetic tone, showed those responding normally to training (82.76 ms, 95% confidence interval 77.75-87.78) to be significantly different to those showing a decrease (45.97 ms, 95% confidence interval, 30.79-61.14) or hyper-responsiveness (160.44 ms, 95% confidence interval, 142.02-178.85; all, p < 0.001). Similar results were observed for mixed sympathetic and parasympathetic signal standard deviation of the NN intervals (ms): normal (65.39; 95% confidence interval, 62.49-68.29), decrease (40.07; 95% confidence interval, 29-51.14), and hyperresponse (115.00; 95% confidence interval, 105.46-124.54; all, p < 0.001) and synonymous frequency domain components. An examination of the 95% confidence interval shows a narrow band surrounding a normal response compared with broader bands accompanying adverse responses. Thus, severe perturbations both above and below normal responses lasting >2 weeks indicated an athlete`s transition to NFOR and, hence, are useful for assessing possible overreaching/training.